A multi-biomarker approach in cross-transplanted mussels Mytilus galloprovincialis - Serafim, M.A. (2020)
The present work integrates the active biomonitoring (ABM) concept in mussels Mytilus galloprovincialis from the South coast of Portugal transplanted during 28 days between two sites with different sources of contamination, and vice versa, in order to assess biological effects in these mussels. For that purpose a multibiomarker approach was used. The suit of biomarkers indicative of metal contamination were metallothioneins (MT) and the enzyme δ-aminolevulinic acid dehydratase (ALAD), for organic contamination mixed function oxidase system (MFO), glutathione-S-transferase (GST) and acetylcholinesterase (AChE), as oxidative stress biomarkers superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and lipid peroxidation (LPO). These biomarkers were used to determine an index to evaluate the stress levels in these two sites. Site A is strongly influenced by metallic contamination, with higher Cu, Cr and Pb in M. galloprovincialis, as well as higher MT levels, antioxidant enzymes activities and LPO concentrations, and lower ALAD activity. In site B organic compounds (PAHs) are prevalent and native mussels show higher activities of the MFO system components and GST. Transplanted mussels had significant alterations in some biomarkers that reflect the type of contaminants present in each site, which demonstrates the primary role of the environment in determining the physiological characteristics of resident mussels. Therefore the application of ABM using a battery of biomarkers turns out to be a useful approach in sites where usually complex mixtures of contaminants occurs. In this study the biomarkers that better differentiate the impact of different contaminants at each site were MT, CYP450, SOD and CAT.